NILAI MORAL DALAM CERITA ASAL USUL SUNGAI KAWAT DAN CERITA BUJANG BEJI DARI KABUPATEN SINTANG - Fitriyani, Ellma; Martono, Martono; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract This research is motivated by researchers' activities to analyze Moral Values in the Origins of the Wire River and the Bujang Beji Story. There is a rapid change in moral values so that many people do not have an idea about the norm of goodness and the development of regional oral literature whose development is not as fast as it used to be. The research method used in this study is a descriptive and qualitative method withinterview and recording techniques. In this study, there are three moral values, namely religious moral values, individual moral values, and social moral values. Religious moral values consist of praying, giving thanks, belief in God Almighty, believing in God's destiny, weak human beings, and pious attitudes. Individual moral values consist of diligence, responsibility, intelligence, patience, sincerity, selfishness and greed,suffering, hope, obedience, and honesty. Social moral values consist of helping, affection, giving advice and courage. The results of this research can be used in learning Folklore. Researchers compile RPP with Discovery Learning model with Scientific approach. Keywords: Folklore, Moral, Values